High-performance water-dispersible tunnel coating full-automatic production process
Patent Information
- Application Number
- CN202610863821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-15
AI Technical Summary
由于隧道环境相对封闭,发生火灾时温度迅速上升,严重威胁隧道路面和衬砌强度,现有的隧道涂料,在耐高温效果和燃烧产物的特性上,会产生很多对人体有害的气体,另外,隧道内设施表面长期积累的灰尘、污渍等难以及时清洗,滋生有害微生物和细菌,影响隧道环境卫生
1.本发明提供的高性能水分散型隧道涂料全自动生产工艺,涂料生产工艺上采用液体计量器计量,卧式砂磨机,高速分散机,半自动灌装整套工艺流程,从投料到出成品一道工序,生产效率高,并且生产出的高性能水分散型隧道涂料,该涂料应用在隧道中具备优异的阻燃,耐腐蚀和耐水的特点。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology, specifically a fully automated production process for high-performance water-dispersible tunnel coatings. Background Technology
[0002] Tunnels are typically roads created by excavating or quarrying rocks underground. Because tunnel construction can minimize distances, reduce land occupation, and significantly reduce environmental impact, they play a crucial role in road planning and construction. Tunnel construction requires concrete for the inner walls, but concrete strength decreases significantly with increasing temperature. Due to the tunnel's unique structure, temperatures inside a tunnel can typically exceed 1000°C in the event of a fire. The masonry structure inside a tunnel is often unable to withstand such high temperatures, potentially leading to tunnel collapse and serious accidents and casualties. Therefore, fireproofing and heat insulation design for the tunnel interior are critical considerations during tunnel construction. Because the tunnel environment is relatively enclosed, the temperature rises rapidly when a fire occurs, seriously threatening the strength of the tunnel pavement and lining. Existing tunnel coatings, in terms of high-temperature resistance and the characteristics of combustion products, produce many gases that are harmful to the human body. In addition, dust and stains that accumulate on the surface of facilities inside the tunnel over a long period of time are difficult to clean in time, breeding harmful microorganisms and bacteria, affecting the hygiene of the tunnel environment.
[0003] Chinese patent CN116004065B discloses a tunnel diffuse reflection coating and its preparation method. The flame retardant prepared by this invention decomposes into phosphoric acid, metaphosphoric acid or polymetaphosphoric acid under high temperature conditions, forming an organic carbon residue layer covering the material surface, which hinders or delays the combustion rate of the polymer and improves the flame retardant performance of the tunnel diffuse reflection coating. However, in this solution, during the long-term service of the coating, the flame retardant components will gradually migrate, resulting in a decrease in flame retardant ability. Summary of the Invention
[0004] The purpose of this invention is to provide a fully automated production process for high-performance water-dispersible tunnel coatings. The coating production process employs a liquid metering device, a horizontal sand mill, a high-speed disperser, and a semi-automatic filling process, completing the entire process from material input to finished product output in one step, resulting in high production efficiency. Mica powder is modified by citric acid etching to expand the interlayer spacing of mica and increase the specific surface area. It is then grafted with castor oil polyether polyol and placed in an interpenetrating structure formed by polyurethane and styrene resin. This effectively prevents the migration of ammonium polyphosphate, an effective flame retardant component in the coating, due to long-term use. Furthermore, the ammonium polyphosphate exists in a core-shell structure with a zinc metal skeleton as the shell, which effectively extends the effective time of the flame retardant component.
[0005] The objective of this invention can be achieved through the following technical solutions: The fully automated production process for high-performance water-dispersible tunnel coatings includes the following steps: Step 1: Modify mica with citric acid to obtain modified mica powder, and then graft it with castor oil polyether polyol to obtain castor oil / modified mica powder.
[0006] Step 2: Using castor oil / modified mica powder as the matrix, a core-shell structure with ammonium polyphosphate as the core and zinc metal skeleton as the shell is deposited on the surface to obtain the composite flame retardant coating precursor. Then, the composite flame retardant coating is placed in the interpenetrating structure formed by polyurethane and styrene resin to obtain the composite flame retardant coating.
[0007] Step 3: Add the composite flame-retardant coating into the pulping tank, then add cellulose and deionized water, stir, and grind to obtain a high-performance water-dispersible tunnel coating semi-finished product.
[0008] Step 4: Place the high-performance water-dispersible tunnel coating semi-finished product into the paint mixing system, then add the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester, and stir thoroughly to obtain the high-performance water-dispersible tunnel coating; output to the filter, and after filtration, weigh, fill into barrels, cap and label them through a semi-automatic filling system, indicating the name, model, specifications, production date, shelf life and other information of the coating, thus completing the fully automatic production process of the high-performance water-dispersible tunnel coating.
[0009] Furthermore, the specific preparation steps of the modified mica powder are as follows: Mica powder, citric acid, and deionized water were added to a reaction vessel and stirred for 3-4 hours at 70-75℃ and 500-600 r / min. The mixture was then filtered, and the filter cake was washed with deionized water until the final washing liquid was neutral. The mixture was then vacuum dried at 60-70℃ for 8-9 hours to obtain modified mica powder.
[0010] Furthermore, the ratio of mica powder, citric acid, and deionized water is 1-2 kg: 800-900 g: 4-5 L.
[0011] Furthermore, the specific preparation steps for castor oil / modified mica powder are as follows: Modified mica powder and formaldehyde solution were added to a reaction vessel and ultrasonically dispersed for 40-60 min. Then castor oil polyether polyol and triethylamine were added and stirred for 1-2 h at 70-80℃ and 400-600 r / min. The mixture was filtered, and the filter cake was washed 2-4 times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60-70℃ for 1-2 h to obtain castor oil / modified mica powder.
[0012] Furthermore, the ratio of modified mica powder, formaldehyde solution, castor oil polyether polyol and triethylamine is 1-2 kg: 3-4 L: 800-900 g: 200-300 mL.
[0013] Furthermore, the specific preparation steps of the composite flame retardant masterbatch precursor are as follows: Ammonium polyphosphate, 2,5-diaminobenzoic acid, and deionized water were added to a polytetrafluoroethylene reactor. Sodium hexadecyl sulfate was dissolved in a 50-60 wt% ethanol solution and then added to the reactor. The mixture was stirred at 120-140℃ and 400-500 r / min for 40 min. Zinc chloride and castor oil / modified mica powder were then added, and the mixture was stirred and reacted for another 3 h. The mixture was then filtered, and the filter cake was washed 2-4 times with deionized water and anhydrous ethanol, respectively. The mixture was then vacuum dried at 60-70℃ for 1-2 h to obtain the composite flame retardant masterbatch precursor.
[0014] Furthermore, the ratio of ammonium polyphosphate, 2,5-diaminobenzoic acid, deionized water, sodium hexadecyl sulfate, ethanol solution, zinc chloride, and castor oil / modified mica powder is 500-600g: 1-2kg: 2-3L: 50-60g: 800-900mL: 200-300g: 1-2kg.
[0015] Furthermore, the specific preparation steps of the composite flame-retardant coating are as follows: The composite flame retardant masterbatch precursor, polyether polyol, and deionized water are added to a reaction vessel and stirred for 20-30 minutes at 20-25℃ and 500-600 r / min. Styrene resin powder with a particle size of 30-40 μm is dissolved in acetone and added to the reaction vessel. Stirring is continued for 40-60 minutes. Isocyanate and a 0.3% (w / w) dibutyltin dilaurate solution are then added, and the reaction is continued for 1-2 hours. The mixture is filtered, and the filter cake is washed 2-4 times with deionized water and anhydrous ethanol, respectively. The mixture is then vacuum dried at 60-70℃ for 1-2 hours to obtain the composite flame retardant coating.
[0016] Furthermore, the ratio of the amount of composite flame retardant masterbatch precursor, polyether polyol, deionized water, styrene resin powder, acetone, isocyanate and dibutyltin dilaurate solution is 800-900g: 2-3L: 8-9L: 200-300g: 800-900mL: 1-2L: 100-200mL.
[0017] Furthermore, the specific preparation steps for the high-performance water-dispersible tunnel coating semi-finished product are as follows: Pour the composite flame-retardant coating into the powder tank, open the vacuum valve, and when the negative pressure value on the vacuum gauge reaches 0.06-0.08 MPa, close the vacuum valve. Then open the powder valve to allow the powder to be sucked into the slurry tank. When the negative pressure value is lower than 0.04-0.05 MPa, close the powder valve and then open the vacuum valve again. Start the vacuum pump power supply. When the negative pressure value reaches 0.06-0.08 MPa, close the vacuum valve again. Repeat the cycle until the powder is completely washed into the slurry tank. Add cellulose and deionized water to the slurry tank and stir evenly. Disperse at high speed at 2000-2200 r / min for 5-6 minutes. Start the horizontal sand mill and grind for 30-40 minutes to obtain a high-performance water-dispersible tunnel coating semi-finished product.
[0018] Furthermore, the specific preparation steps for the high-performance water-dispersible tunnel coating are as follows: The high-performance water-dispersible tunnel coating semi-finished product is injected into the paint mixing system, and then the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester are added to the paint mixing system in sequence. The mixture is then dispersed at high speed of 2000-2200 r / min for 5-6 min to obtain the high-performance water-dispersible tunnel coating.
[0019] The beneficial effects of this invention are: 1. The fully automated production process for high-performance water-dispersible tunnel coatings provided by this invention employs a liquid metering device, a horizontal sand mill, a high-speed disperser, and a semi-automatic filling process. The entire process, from material feeding to finished product output, is completed in one step, resulting in high production efficiency. The high-performance water-dispersible tunnel coating produced exhibits excellent flame retardancy, corrosion resistance, and water resistance when applied in tunnels.
[0020] 2. This invention relates to a high-performance water-dispersible tunnel coating. Mica powder is modified by citric acid etching to increase the interlayer spacing and specific surface area. It is then grafted with castor oil polyether polyol. The lubricity of castor oil reduces friction between mica particles, preventing coating brittleness. The long alkyl chains of castor oil impart hydrophobicity to mica, significantly improving its compatibility with the interpenetrating structure formed by polyurethane and styrene resins, preventing filler agglomeration, and enhancing the overall hydrophobic effect of the coating. Furthermore, the interpenetrating structure effectively prevents the migration of ammonium polyphosphate, an effective flame-retardant component, during long-term use. The ammonium polyphosphate exists in a core-shell structure with a zinc metal framework, which effectively extends the effective time of the flame-retardant component. The metal framework also promotes the char formation of ammonium polyphosphate during its flame-retardant action. The zinc metal framework, under normal conditions, possesses certain antibacterial properties, imparting antibacterial capabilities to the coating and preventing bacterial growth in the tunnel. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1: A fully automated production process for high-performance water-dispersible tunnel coatings, comprising the following steps: S1: Add 1 kg of mica powder, 800 g of citric acid and 4 L of deionized water to a reaction vessel, stir for 3 h at 70 °C and 500 r / min, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 60 °C for 8 h to obtain modified mica powder.
[0023] S2: Add 1 kg of modified mica powder and 3 L of formaldehyde solution to a reaction vessel, ultrasonically disperse for 40 min, then add 800 g of castor oil polyether polyol and 200 mL of triethylamine, stir for 1 h at 70 °C and 400 r / min, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 60 °C for 1 h to obtain castor oil / modified mica powder.
[0024] S3: Add 500g of ammonium polyphosphate, 1kg of 2,5-diaminobenzoic acid and 2L of deionized water to a polytetrafluoroethylene reactor. Dissolve 50g of sodium hexadecyl sulfate in 800mL of 50wt% ethanol solution and add it to the reactor. Stir at 120℃ and 400r / min for 40min. Then add 200g of zinc chloride and 1kg of castor oil / modified mica powder. Continue stirring and react for 3h. Filter and wash the filter cake twice with deionized water and anhydrous ethanol, respectively. Dry under vacuum at 60℃ for 1h to obtain the composite flame retardant coating precursor.
[0025] S4: Add 800g of composite flame retardant coating precursor, 2L of polyether polyol and 8L of deionized water to a reaction vessel and stir for 20min at 20℃ and 500r / min. Add 200g of styrene resin powder with a particle size of 30μm and 800mL of acetone to the reaction vessel and stir until dissolved. Continue stirring for 40min. Then add 1L of isocyanate and 100mL of 0.3% dibutyltin dilaurate solution and continue stirring for 1h. Filter and wash the filter cake twice with deionized water and anhydrous ethanol, respectively. Dry under vacuum at 60℃ for 1h to obtain the composite flame retardant coating.
[0026] S5: Pour the composite flame-retardant coating into the powder tank, open the vacuum valve, and when the negative pressure value on the vacuum gauge reaches 0.06 MPa, close the vacuum valve. Then open the powder valve to allow the powder to be sucked into the slurry tank. When the negative pressure value is lower than 0.04 MPa, close the powder valve and then open the vacuum valve again. Start the vacuum pump power supply. When the negative pressure value reaches 0.06 MPa, close the vacuum valve again. Repeat the cycle until the powder is completely washed into the slurry tank. Add cellulose and deionized water to the slurry tank and stir evenly. Disperse at high speed at 2000 r / min for 5 minutes. Start the horizontal sand mill and grind for 30 minutes to obtain a high-performance water-dispersible tunnel coating semi-finished product.
[0027] S6: First, inject the semi-finished high-performance water-dispersible tunnel coating into the paint mixing system, then add the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester into the paint mixing system in sequence, and disperse at high speed of 2000r / min for 5min to obtain the high-performance water-dispersible tunnel coating; place the high-performance water-dispersible tunnel coating in a filter, and after filtration, weigh, fill and cap it through a semi-automatic filling system. Label the outer packaging of the high-performance water-dispersible tunnel coating, indicating the name, model, specifications, production date and shelf life information of the coating, and complete the fully automatic production process of the high-performance water-dispersible tunnel coating.
[0028] Example 2: Fully automated production process for high-performance water-dispersible tunnel coatings, comprising the following steps: S1: Add 1.5 kg mica powder, 850 g citric acid and 4.5 L deionized water to a reaction vessel, stir for 3.5 h at 72.5 °C and 550 r / min, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 65 °C for 8.5 h to obtain modified mica powder.
[0029] S2: Add 1.5 kg of modified mica powder and 3.5 L of formaldehyde solution to a reaction vessel and ultrasonically disperse for 50 min. Then add 850 g of castor oil polyether polyol and 250 mL of triethylamine. Stir for 1.5 h at 75 °C and 500 r / min. Filter the mixture and wash the filter cake three times with deionized water and anhydrous ethanol, respectively. Dry the mixture under vacuum at 65 °C for 1.5 h to obtain castor oil / modified mica powder.
[0030] S3: Add 550g of ammonium polyphosphate, 1.5kg of 2,5-diaminobenzoic acid and 2.5L of deionized water to a polytetrafluoroethylene reactor. Dissolve 55g of sodium hexadecyl sulfate in 850mL of 55wt% ethanol solution and add it to the reactor. Stir at 130℃ and 450r / min for 40min. Then add 250g of zinc chloride and 1.5kg of castor oil / modified mica powder. Continue stirring and react for 3h. Filter and wash the filter cake three times with deionized water and anhydrous ethanol respectively. Vacuum dry at 65℃ for 1.5h to obtain the composite flame retardant coating precursor.
[0031] S4: Add 850g of composite flame retardant coating precursor, 2.5L of polyether polyol and 8.5L of deionized water to a reaction vessel and stir for 25min at 22.5℃ and 550r / min. Dissolve 250g of styrene resin powder with a particle size of 35μm in 850mL of acetone and add it to the reaction vessel. Continue stirring for 50min. Then add 1.5L of isocyanate and 150mL of 0.3% dibutyltin dilaurate solution and continue stirring for 1.5h. Filter and wash the filter cake three times with deionized water and anhydrous ethanol respectively. Dry under vacuum at 65℃ for 1.5h to obtain the composite flame retardant coating.
[0032] S5: Pour the composite flame-retardant coating into the powder tank, open the vacuum valve, and when the negative pressure value on the vacuum gauge reaches 0.07 MPa, close the vacuum valve. Then open the powder valve to allow the powder to be sucked into the slurry tank. When the negative pressure value is lower than 0.045 MPa, close the powder valve and then open the vacuum valve again. Start the vacuum pump power supply. When the negative pressure value reaches 0.07 MPa, close the vacuum valve again. Repeat the cycle until the powder is completely washed into the slurry tank. Add cellulose and deionized water to the slurry tank and stir evenly. Disperse at high speed at 2100 r / min for 5.5 min. Start the horizontal sand mill and grind for 35 min to obtain a high-performance water-dispersible tunnel coating semi-finished product.
[0033] S6: First, inject the semi-finished high-performance water-dispersible tunnel coating into the paint mixing system, then add the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester into the paint mixing system in sequence, and disperse at high speed of 2100r / min for 5.5min to obtain the high-performance water-dispersible tunnel coating; place the high-performance water-dispersible tunnel coating in a filter, and after filtration, weigh, fill and cap it through a semi-automatic filling system. Label the outer packaging of the high-performance water-dispersible tunnel coating, indicating the name, model, specifications, production date and shelf life information of the coating, and complete the fully automatic production process of the high-performance water-dispersible tunnel coating.
[0034] Example 3: A fully automated production process for high-performance water-dispersible tunnel coatings, comprising the following steps: S1: Add 2 kg of mica powder, 900 g of citric acid and 5 L of deionized water to a reaction vessel, stir for 4 h at 75 °C and 600 r / min, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and dry under vacuum at 70 °C for 9 h to obtain modified mica powder.
[0035] S2: Add 2 kg of modified mica powder and 4 L of formaldehyde solution to a reaction vessel and ultrasonically disperse for 60 min. Then add 900 g of castor oil polyether polyol and 300 mL of triethylamine. Stir for 2 h at 80 °C and 600 r / min. Filter the mixture and wash the filter cake four times with deionized water and anhydrous ethanol, respectively. Dry the mixture under vacuum at 70 °C for 2 h to obtain castor oil / modified mica powder.
[0036] S3: Add 600g of ammonium polyphosphate, 2kg of 2,5-diaminobenzoic acid and 3L of deionized water to a polytetrafluoroethylene reactor. Dissolve 60g of sodium hexadecyl sulfate in 900mL of 60wt% ethanol solution and add it to the reactor. Stir at 140℃ and 500r / min for 40min. Then add 300g of zinc chloride and 2kg of castor oil / modified mica powder. Continue stirring and react for 3h. Filter and wash the filter cake 4 times with deionized water and anhydrous ethanol respectively. Dry under vacuum at 70℃ for 2h to obtain the composite flame retardant coating precursor.
[0037] S4: Add 900g of composite flame retardant coating precursor, 3L of polyether polyol and 9L of deionized water to a reaction vessel and stir for 30min at 25℃ and 600r / min. Add 300g of styrene resin powder with a particle size of 40μm and 900mL of acetone to the reaction vessel and stir until dissolved. Continue stirring for 60min. Then add 2L of isocyanate and 200mL of 0.3% dibutyltin dilaurate solution and continue stirring for 2h. Filter and wash the filter cake 4 times with deionized water and anhydrous ethanol respectively. Dry under vacuum at 70℃ for 2h to obtain the composite flame retardant coating.
[0038] S5: Pour the composite flame-retardant coating into the powder tank, open the vacuum valve, and when the negative pressure value on the vacuum gauge reaches 0.08 MPa, close the vacuum valve. Then open the powder valve to allow the powder to be sucked into the slurry tank. When the negative pressure value is lower than 0.05 MPa, close the powder valve and then open the vacuum valve again. Start the vacuum pump power supply. When the negative pressure value reaches 0.08 MPa, close the vacuum valve again. Repeat the cycle until the powder is completely washed into the slurry tank. Add cellulose and deionized water to the slurry tank and stir evenly. Disperse at high speed at 2200 r / min for 6 minutes. Start the horizontal sand mill and grind for 40 minutes to obtain a high-performance water-dispersible tunnel coating semi-finished product.
[0039] S6: First, inject the semi-finished high-performance water-dispersible tunnel coating into the paint mixing system, then add the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester into the paint mixing system in sequence, and disperse at high speed of 2200r / min for 6min to obtain the high-performance water-dispersible tunnel coating; place the high-performance water-dispersible tunnel coating in a filter, and after filtration, weigh, fill and cap it through a semi-automatic filling system. Label the outer packaging of the high-performance water-dispersible tunnel coating, indicating the name, model, specifications, production date and shelf life information of the coating, and complete the fully automatic production process of the high-performance water-dispersible tunnel coating.
[0040] In this embodiment and comparative example: In the fully automated production process of high-performance water-dispersible tunnel coatings, all liquids are weighed using liquid metering devices, grinding is done using a horizontal sand mill, and high-speed dispersion is done using a high-speed disperser.
[0041] Comparative Example 1: Based on Example 3, other steps remain unchanged, except for step S1, and the modified mica powder in step S2 is replaced with mica powder.
[0042] Comparative Example 2: Based on Example 3, other steps remain unchanged, except for step S2, and castor oil / modified mica powder in step S3 is replaced with modified mica powder in step S1.
[0043] Comparative Example 3: Based on Example 3, other steps remain unchanged, step S4 is deleted, and the composite flame retardant coating precursor in step S3 is directly processed in step S5.
[0044] The performance of the high-performance water-dispersible tunnel coatings obtained in Examples 1-3 and Comparative Examples 1-3 was tested according to standard GB 28375-2012, with a measured coating thickness of 10 mm. After the experiment, the coatings did not crack, delaminate, or peel; slight swelling and discoloration were permissible. The test results are shown in Table 1. Table 1 Performance Test Table for High-Performance Water-Dispersible Tunnel Coatings
[0045] As can be seen from Table 1, the high-performance water-dispersible tunnel coatings obtained in Examples 1-3 have significantly better water resistance, acid resistance, damp heat resistance, and fire resistance than the comparative examples. This indicates that the high-performance water-dispersible tunnel coatings prepared by the fully automated production process provided by the present invention have excellent flame retardancy, corrosion resistance, and water resistance when applied in tunnels.
[0046] In Comparative Example 1, the modified mica powder was replaced with mica powder, demonstrating that the mica powder, through citric acid etching modification, can expand the interlayer spacing of mica and increase the specific surface area. The modified mica powder is more likely to load the core-shell structure formed by ammonium polyphosphate and zinc metal skeleton, but it does not have a substantial impact on the overall performance, so the performance in the test is acceptable.
[0047] In Comparative Example 2, castor oil / modified mica powder was replaced with modified mica powder. This demonstrates that after graft modification with castor oil polyether polyol, the lubricity of castor oil can reduce friction between mica particles, preventing coating brittleness. The long alkyl chain of castor oil imparts hydrophobicity to mica, significantly improving its compatibility with the interpenetrating structure formed by polyurethane and styrene resins, preventing filler agglomeration, and improving the overall hydrophobic effect of the coating. Without the modification of castor oil, the water resistance will decrease significantly.
[0048] Comparative Example 3 directly omits further processing of the composite flame-retardant coating precursor, demonstrating that the formation of interpenetrating structures can effectively prevent the migration of ammonium polyphosphate caused by the effective flame-retardant components in the coating during long-term use. Furthermore, the ammonium polyphosphate exists in a core-shell structure with a zinc metal skeleton as the shell. This structure can effectively improve the effective time of the flame-retardant components, and the metal skeleton can promote the char formation ability of ammonium polyphosphate when it exerts its flame-retardant effect.
[0049] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A fully automated production process for high-performance water-dispersible tunnel coatings, characterized in that: Includes the following steps: Step 1: Modify mica with citric acid to obtain modified mica powder, and then graft it with castor oil polyether polyol to obtain castor oil / modified mica powder. Step 2: Using castor oil / modified mica powder as the matrix, a core-shell structure with ammonium polyphosphate as the core and zinc metal skeleton as the shell is deposited on the surface to obtain the composite flame retardant coating precursor. Then, the composite flame retardant coating is placed in the interpenetrating structure formed by polyurethane and styrene resin to obtain the composite flame retardant coating. Step 3: Add the composite flame-retardant coating into the pulping tank, then add cellulose and deionized water, stir, and grind to obtain a high-performance water-dispersible tunnel coating semi-finished product; Step 4: Place the semi-finished high-performance water-dispersible tunnel coating into the paint mixing system, then add the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester, and stir thoroughly to obtain the high-performance water-dispersible tunnel coating; output to the filter, and after filtration, weigh, fill into barrels, cap and label them through a semi-automatic filling system, indicating the name, model, specifications, production date and shelf life of the coating, thus completing the fully automated production process of the high-performance water-dispersible tunnel coating; The specific preparation steps of the modified mica powder are as follows: Mica powder, citric acid and deionized water are added to a reaction vessel and stirred for 3-4 hours at 70-75℃ and 500-600r / min. The mixture is then filtered, and the filter cake is washed with deionized water until the final washing liquid is neutral. The mixture is then vacuum dried at 60-70℃ for 8-9 hours to obtain modified mica powder. The ratio of mica powder, citric acid, and deionized water is 1-2 kg: 800-900 g: 4-5 L; The specific preparation steps for the castor oil / modified mica powder are as follows: Modified mica powder and formaldehyde solution were added to a reaction vessel and ultrasonically dispersed for 40-60 min. Then castor oil polyether polyol and triethylamine were added and stirred for 1-2 h at 70-80℃ and 400-600 r / min. The mixture was filtered, and the filter cake was washed 2-4 times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60-70℃ for 1-2 h to obtain castor oil / modified mica powder. The ratio of modified mica powder, formaldehyde solution, castor oil polyether polyol and triethylamine is 1-2 kg: 3-4 L: 800-900 g: 200-300 mL; The specific preparation steps of the composite flame-retardant coating precursor are as follows: Ammonium polyphosphate, 2,5-diaminobenzoic acid, and deionized water were added to a polytetrafluoroethylene reactor. Sodium hexadecyl sulfate was dissolved in a 50-60 wt% ethanol solution and then added to the reactor. The mixture was stirred at 120-140℃ and 400-500 r / min for 40 min. Zinc chloride and castor oil / modified mica powder were then added, and the mixture was stirred and reacted for another 3 h. The mixture was then filtered, and the filter cake was washed 2-4 times with deionized water and anhydrous ethanol, respectively. The mixture was then vacuum dried at 60-70℃ for 1-2 h to obtain the precursor of the composite flame retardant coating. The ratio of the following components is: ammonium polyphosphate, 2,5-diaminobenzoic acid, deionized water, sodium hexadecyl sulfate, ethanol solution, zinc chloride, and castor oil / modified mica powder: 500-600g: 1-2kg: 2-3L: 50-60g: 800-900mL: 200-300g: 1-2kg. The specific preparation steps of the composite flame-retardant coating are as follows: The composite flame retardant coating precursor, polyether polyol, and deionized water are added to a reaction vessel and stirred for 20-30 minutes at 20-25℃ and 500-600 r / min. Styrene resin powder with a particle size of 30-40 μm and acetone are stirred and dissolved and then added to the reaction vessel. Stirring is continued for 40-60 minutes. Isocyanate and a 0.3% (w / w) dibutyltin dilaurate solution are then added and the reaction is continued for 1-2 hours. The mixture is filtered, and the filter cake is washed 2-4 times with deionized water and anhydrous ethanol, respectively. The mixture is then vacuum dried at 60-70℃ for 1-2 hours to obtain the composite flame retardant coating. The ratio of the amount of the composite flame retardant coating precursor, polyether polyol, deionized water, styrene resin powder, acetone, isocyanate and dibutyltin dilaurate solution is 800-900g: 2-3L: 8-9L: 200-300g: 800-900mL: 1-2L: 100-200mL. The specific preparation steps for the high-performance water-dispersible tunnel coating semi-finished product are as follows: Pour the composite flame-retardant coating into the powder tank, open the vacuum valve, and when the negative pressure value on the vacuum gauge reaches 0.06-0.08 MPa, close the vacuum valve. Then open the powder valve to allow the powder to be sucked into the slurry tank. When the negative pressure value is lower than 0.04-0.05 MPa, close the powder valve and then open the vacuum valve again. Start the vacuum pump power supply. When the negative pressure value reaches 0.06-0.08 MPa, close the vacuum valve again. Repeat the cycle until the powder is completely washed into the slurry tank. Add cellulose and deionized water to the slurry tank and stir evenly. Disperse at high speed at 2000-2200 r / min for 5-6 minutes. Start the horizontal sand mill and grind for 30-40 minutes to obtain a high-performance water-dispersible tunnel coating semi-finished product. The specific preparation steps of the high-performance water-dispersible tunnel coating are as follows: The high-performance water-dispersible tunnel coating semi-finished product is injected into the paint mixing system, and then the leveling agent polyacrylate and the film-forming aid dodecyl alcohol ester are added to the paint mixing system in sequence. The mixture is then dispersed at high speed of 2000-2200 r / min for 5-6 min to obtain the high-performance water-dispersible tunnel coating.
Citation Information
Patent Citations
A tunnel diffuse reflection coating and its preparation method
CN116004065B
Multifunctional coatings and preparation method thereof
CN101386719A
Expanded type fireproof coating and preparation method thereof
CN101659823A